Taṭwir Kitab al-Qirā’ah al-Rasyīdah bi al-Șuwar - Siti Wasilah Juhra; Moch. Fajarul Falah (DAYAH: Journal of Islamic Education, 2018)
The learning proses head for obtain the knowledge, skill and ability. Teachers, students and curriculum are substance of learning, and textbook was included in curriculum. The textbook has an important role as the source of knowledges, and informations. A good textbook is a fun and inspiration textbook, therefore the researcher wants to develop al-Qirᾱ’at al-Rasyidah textbook by drawing, because the textbook was not interest for students. The researcher wanted to explain the steps for this research, the problems during the research, and the effectiveness of product in this study. This study depanded on research and development metho, and This study based on quantitative and qualitative approach. This study used test, questionnaire, interview, and t-test related for data record.This study was conducted in accordance with the measures in the research and development method, although there are some problems during the implementation of this study, such as the difficulty of finding an ilustrator, and edit the original drawing to be an attractive and a suitable media in the textbook. However, the developed al-Qirᾱ’at al-Rasyidah book already effective for students. This is shown by student learning outcomes in this product experiment, which the result from the T-tes related calculation is greater than T-tabel result.